Passive Acoustic Measurement of Bedload Transport: Toward a Global Calibration Curve?. Issue 8 (3rd August 2020) - Geay, T.; Zanker, S.; Misset, C.; Recking, A.
Abstract: Bedload transport is recognized as a key process in the development of river channel forms; however, most rivers suffer from an absence of data. Performing bedload measurements to document bedload transport rates is a challenge, as the deployment of traditional bedload samplers is time consuming and risky in floods. Consequently, bedload measurements are rarely executed. Alternative techniques are being developed to complement the use of traditional bedload measurements and to provide continuous monitoring. Passive acoustic measurements are made with hydrophones, measuring the underwater sounds naturally generated by bedload impacts in rivers. This paper proposes an innovative deployment of hydrophones to record bedload sounds at the scale of a cross section. The measured acoustic signals are interpreted with bedload samplings and with hydraulic and river bed parameters. Field experiments were done in 14 different sites, exploring a diversity of rivers. Bedload flux was observed to be the most consistent variable explaining the monitored acoustic power. Based on 25 experiments on 14 rivers, the cross‐section‐averaged acoustic power was related to the specific bedload flux and showed a good agreement (60% of bedload flux estimated within a factor of 2). The robustness of the obtained calibration curve remains to be tested. However, the potential of passive acoustic profiles to provide a continuous measurement of bedload sounds that could be used in the development of bedload gauging stations is shown. Key Points: Using cross‐averaged values, the power of bedload self‐generated noise was related to sampled bedload flux at 14 different sites. The spectral analysis of bedload self‐generated noise shows that the acoustic measurements are affected by propagation effects Uncertainties on physical bedload measurements limit the understanding of indirect measurements of bedload transport